Determining the Validity and Reliability of the Arabic Version of the Cognitive Flexibility Questionnaire Among Iraqi Volleyball Players: A Psychometric Study - Mohammed Alawadi, Mohammed Kamil; Meshkati, Zohreh; Kadhim Alkurdi, Raafat Abdulhadi; Serjuei, Zahra; Ahmadi, Pezhman (Mental Health and Lifestyle Journal, 2026)
Cognitive flexibility, as one of the core components of executive functions, plays a crucial role in adapting and responding to changing and challenging conditions and is considered a key factor influencing success in team sports such as volleyball. The instrument commonly used to assess cognitive flexibility is the Cognitive Flexibility Questionnaire. The aim of this study was to determine the validity and reliability of the Arabic version of the Cognitive Flexibility Questionnaire developed by Dennis and Vander Wal (2010) and to examine its applicability among male volleyball players in Iraq. The statistical population consisted of 230 male volleyball players with at least three years of regular training experience, selected through convenience sampling. Data were collected using the translated 20-item version of the Cognitive Flexibility Questionnaire. Construct validity was assessed using Confirmatory Factor Analysis (CFA), and reliability was evaluated using Cronbach’s alpha coefficient and Composite Reliability (CR) in AMOS and SPSS software. The significance level was set at 0.05. The results supported the goodness-of-fit indices of the three-factor structure of the questionnaire (GFI = 0.90, CFI = 0.93, RMSEA = 0.07, χ²/df = 2.5). Moreover, the internal consistency of the entire questionnaire was reported as 0.89, and for its subscales, it ranged between 0.83 and 0.87, indicating high validity and reliability of the instrument in the studied population. Therefore, the Arabic version of this questionnaire demonstrates appropriate applicability for use in sports psychology research and the assessment of cognitive flexibility among Arabic-speaking populations. It is recommended that longitudinal studies be conducted to examine long-term stability.